Impact Associated with the Lack of Centralized Sewerage Treatment Systems and Inadequate Operation of Available Decentralized Treatment Systems, a Source of Emerging Contaminants in Urban Water Resources: A Review Case Study of Kigali City Rwanda, a Reflection of Other East African Countries' Cities - Bavumiragira , Jean Pierre; Yin , Hailong; Kipkrui , Edwin; Uyisaba , Pascaline; Ndizeye , Yves; Bazambanza , Alex (Emerging Issues in Environment, Geography and Earth Science Vol. 2, 2023)
The purpose of this paper is to review the effects of inadequately operating decentralized sewage treatment systems, lack of sewerage systems/networks and their centralized sewage treatment systems, and improper disposal of solid and liquid waste (sewage mixed with other hazardous processed chemicals from septic tanks or toilets) on the aquatic environment (surface water and groundwater) and human life. As a result of the lack of a sewerage system or network in the country, 81.6% of the improved sanitation in Rwanda uses pit latrines with solid slabs, according to the census report of household living conditions EICV 4 that was approved by the Rwanda National Institute of Statistics in March 2016. High-altitude topography has significantly contaminated surface and groundwater in a number of locations, including the capital city of Kigali. The complexity of wastewater management has also been exacerbated by the high level of life in the area and the absence of government financing for the creation of various initiatives for centralized sanitation. A count of 1.3 million people in Kigali means that the city has neither centralized sewage treatment nor central sewage networks. Except for a few semi-centralized sewage treatment systems, septic tanks with soak-away pits are primarily used, together with pit latrines. Due to untreated sewage being disposed inappropriately into the environment, they have potential negative impacts on surface and groundwater resources or in some cases direct discharge to open watercourse. Current examples of streams and rivers receiving inappropriately disposed sewage include Ruganwa, Rwanzekuma, Yanze, and the Mpazi rivers, as well as all tributaries of Nyabugogo River. The problem of water pollution is getting worse as anthropogenic contaminants enter the water cycle. Emerging organic contaminants (EOCs) are of particular concern. For example, pharmaceutical and personal care products are not regulated under current environmental laws. Therefore, they may cause ecological or human health impacts. Since 2016 Kigali city was proposed to have the first centralized sewerage system and construction of wastewater treatment plant through the project named “Rwanda Sustainable Water Supply and Sanitation Program (RSWSSP)”. The final version of the environmental impact assessment (ESIA) received by Rwanda Development Board stated that this problem will be addressed by the RSWSSP program by developing Kigali's first centralized sewerage system, as well as by managing the solid wastes and fecal sludges generated by the 6 satellite cities of Kigali. However, although the project’s ESIA has already been finished it has not been implemented yet. The paper examined the main causes of water pollution in Rwanda's densely populated areas, particularly in the capital city Kigali, the potential effects of a lack of urban centralized sewerage systems, the inadequacy of currently available decentralized technologies to protect human life and the ecosystem, and the public's awareness of the new organic water contaminants that are currently being found in water environments. Also suggested were some of the finest management techniques for safeguarding Rwanda's water resources.